MISCONCEPTION OF STUDENTS ON MULTIPLE REPRESENTATION OF CHEMICAL EQUILIBRIUM SHIFT - Bertalina Timanoyo; Effendy Effendy; Nazriati Nazriati (Pascasarjana Universitas Negeri Malang (UM), 2020)
Abstract: This study aims to analyze students' misconceptions about shifts in chemical equilibrium by using a two-tier multiple choices diagnostic test based on multiple representations. The design of this study is descriptive. The research subjects were second-semester students of Chemistry Department A, B, and I classes in Malang State University in 2018/2019 Academic Year totaling 60 students. The reliability of the diagnostic test is 0.86. The results showed that students' misconceptions of the factors affecting chemical equilibrium shifts identified 9 misconceptions with an average percentage of misconceptions below 30%. Misconceptions also often occur in students when associated with submicroscopic representation. Abstrak: Penelitian ini bertujuan untuk menganalisis miskonsepsi mahasiswa tentang pergeseran kesetimbangan kimia dengan menggunakan tes diagnostik two-tier multiple choice berbasis multipel representasi. Rancangan penelitian ini adalah deskriptif. Subjek penelitian adalah mahasiswa semester 2 Jurusan Kimia kelas A, B dan I Universitas Negeri Malang Tahun Ajaran 2018/2019 yang berjumlah 60 mahasiswa. Reliabilitas tes diagnostik sebesar 0,86. Hasil penelitian menunjukkan bahwa miskonsepsi mahasiswa pada faktor-faktor yang mempengaruhi pergeseran kesetimbangan kimia teridentifikasi 9 miskonsepsi dengan rata-rata persentase miskonsepsi dibawah 30%. Miskonsepsi juga sering terjadi pada mahasiswa apabila dikaitkan dengan representasi submikroskopik